2006
DOI: 10.1291/hypres.29.303
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Subfractions and the Prevalence of Silent Lacunar Infarction in Subjects with Essential Hypertension

Abstract: Recent lipid research has focused on low-density lipoprotein (LDL) subfractions as new markers for cardiovascular risk. However, the clinical significance of measurement of LDL subfractions in subjects with essential hypertension is yet to be established. We studied the association between the prevalence of silent lacunar infarction (SLI) and LDL subfractions in patients with essential hypertension. We performed brain MRI to detect SLI and measured LDL subfractions in 100 asymptomatic non-diabetic middle-aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
21
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 17 publications
4
21
0
1
Order By: Relevance
“…The association of these risk factors with SBIs was not statistically significant, which contrasts with the results of the similar studies on SBIs (18) . Similar results with respect to levels of triglycerides and low HDL levels in association with SBI was also reported by Kato et al (19) . Level of hsCRP is usually reported to be high in SBI indicating the involvement of inflammatory processes (20) , as is also evident in present study.…”
Section: Discussionsupporting
confidence: 90%
“…The association of these risk factors with SBIs was not statistically significant, which contrasts with the results of the similar studies on SBIs (18) . Similar results with respect to levels of triglycerides and low HDL levels in association with SBI was also reported by Kato et al (19) . Level of hsCRP is usually reported to be high in SBI indicating the involvement of inflammatory processes (20) , as is also evident in present study.…”
Section: Discussionsupporting
confidence: 90%
“…First, our population was younger and the majority of our participants was long-term (median 8.6 years since diagnosis) and treated hypertensives with office BP levels that were lower as compared with previous studies selecting hypertensives (Table 1). [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Most importantly, the selection of participants was performed randomly from a primary care setting. The cohort was routinely treated and monitored by general practitioners, avoiding the bias that might be caused by selection in more specialized contexts, such as hospital units.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may be related to this large variation in prevalence. Among all studies, nearly half of them included few participants, and from those with larger sample size (Table 1), [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] it should be noted that patients with hypertension were mainly selected among those who attended specialized units (cardiology, internal medicine, kidney departments, etc) at hospitals and were probably more representative of newly diagnosed or more severe or resistant forms of hypertension than average.…”
mentioning
confidence: 99%
“…However, the relation between hyperlipidemia and SCI has not been clarified. Kato et al recently reported that LDL-3, one of the low-density lipoprotein (LDL) subfraction levels, is a risk factor for SCI in hypertensives (13).…”
mentioning
confidence: 99%
“…The SCI in the white matter might be associated with age and hypertension, while that in the basal ganglia might be paralleled by subclinical systemic atherosclerosis, which also partly determines of the development of coronary atherosclerosis. Kato et al reported that LDL-3 was more strongly associated with the SCI in the basal ganglia than with that in the white matter (13).…”
mentioning
confidence: 99%